Peningkatan Perilaku Pencegahan Demam Berdarah Dengue (DBD) melalui Intervensi Edukasi di Gampong Dayah Mamplam Kecamatan Leupung Aceh Besar - Alfiyaturrahmi, Alfiyaturrahmi; Anwar Arbi; Riza Septiani (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by infection with the DEN-1, DEN-2, DEN-3, or DEN-4 viruses transmitted through the bite of the Aedes aegypti mosquito. This activity aims to see the increase in dengue fever (DHF) prevention behavior through educational interventions in Gampong Dayah Mamplam, Leupung District, Aceh Besar. This activity uses a quantitative method with a cross-sectional design which was carried out from April 29 to May 5, 2024 in Gampong Dayah Mamplam, Leupung District, Aceh Besar. The population was 217 families with a sample size of 70 respondents. Data analysis used the chi-square statistical test. The results showed that 46 female respondents (67.6%) and 40 respondents aged 20-35 years (58.8%). The results of the univariate analysis showed that the largest percentage of prevention behavior was not doing as many as 44 respondents (62.9%). The results of the bivariate analysis showed a relationship between knowledge p-value (0.000), attitude p-value (0.010), education p-value (0.047), work p-value (0.046), the role of health workers p-value (0.001) and family support p-value (0.041) with dengue fever (DHF) prevention behavior in Gampong Dayah Mamplam, Leupung District, Aceh Besar in 2024. The independent variables in this activity have a relationship with DHF prevention behavior. Suggestions are expected that Puskesmas officers and cadres can improve health education regarding DHF and its prevention so that the community can be more positive and act better. It is hoped that the community can independently become mosquito larvae control agents in their own homes.